Treatment patterns and outcomes among mantle cell lymphoma patients treated with ibrutinib in the United States: a retrospective electronic medical record database and chart review study. (23rd October 2020) - Sharman, Jeff; Kabadi, Shaum M.; Clark, Jamyia; Andorsky, David
Summary: The experience of patients with mantle cell lymphoma (MCL) in community oncology practices, including reasons for treatment discontinuation, is sparse. This retrospective study sought to elucidate treatment patterns and outcomes of patients with MCL treated with ibrutinib in the community setting. Patients were identified from the US Oncology Network electronic medical records database, iKnowMed TM, between 1 November 2013 and 31 October 2016. Descriptive analysis was performed to describe the demographic and clinical characteristics of the population. Kaplan–Meier estimates were performed to determine clinical outcomes. A Cox proportional hazards model was used to identify predictors of survival. Of the 1914 patients identified with MCL, 159 were treated with ibrutinib. The median age was 71 years and the majority were male (76%) and Caucasian (89%). The overall discontinuation rate was 83·6%; the most common reasons were progression (35%) and toxicities (25·6%). The median overall survival and progression‐free survival was 25·82 months (95% confidence interval [CI] 19·94, NR) and 19·55 months (95% CI 16·52, 24·28) respectively. In multivariate modelling, patient age was predictive of survival (hazard ratio 1·041, P = 0·0186). Ibrutinib was temporarily reduced in 16·4% ( n = 26) and held in 30·2% ( n = 48), primarily due to toxicity 66·7% ( n = 32). Survival data showed similarities between community oncology practices and clinical trials.